Sistem Monitoring Polusi Udara Mengggunakan Sensor Nitrogen Carbon Berbasis Internet of Thing - Ferry Fachrizal; Julham Julham; Antoni Antoni (STMIK Budi Darma, 2022)
Technological developments in the field of Embedded Systems and Internet Of Thing, can be implemented in a system capable of monitoring air pollution, where the system is capable of transmitting data in real time using sensors located at near or far distances. To transmit data from various sensor devices that are located remotely, the use of LoRA technology is a solution for sending data between the client and the gateway, LoRA communication technology can be implemented into an air pollution monitoring system where the sensors are placed far from the gateway and cloud server. The prototype of this air pollution detector uses an Arduino Uno microcontroller and a Nitrogen Carbon sensor that can detect CO, NO2 and NH3 connected to LoRA Shield with the IoT platform as a monitoring and notification system. The measurement results of the three sensors in this study are displayed on the Smart Phone as a notification. From the research, it was found that the content of NH3 was 1.88ppm, CO was 17.76 ppm and NO2 was 0.12ppm. Based on the Air Pollutant Index, the results of the air quality in this area are not good.